Analisis PSAK No. 18: Akuntansi dan Pelaporan Program Manfaat Purnakarya Terhadap Bank Indonesia - Fadjrihana, Meidah; Apriliani, Rida; Uzilawati, Lia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the pension fund accounting records applied at Bank Indonesia based on the Statement of Accounting Standards (PSAK) No. 18. The type of research used is descriptive qualitative research. Data collection is based on the annual report and financial statements of the Bank Indonesia pension fund for the 2020 and 2021 periods. The analysis technique used in this research uses comparative descriptive which compares the financial statements of the Bank Indonesia pension fund with the Requirements of Accounting Standards (PSAK) No. 18. Based on the research that has been conducted regarding the Application of Accounting Standard Requirements (PSAK) No. 18 regarding pension fund accounting, it can be concluded that the recording and reporting of the Bank Indonesia pension fund is in accordance with the Application of Accounting Standard Requirements (PSAK) No. 18 and there are no deviations from the established standards.